Reliability of two-dimensional kinematics and performance in a battery of lateral hopping tasks in uninjured individuals. - Sasseville, Garrett; Gilgallon, Timothy; Burland, Julie; DiStefano, Michael; Glaviano, Neal R. (Physical Therapy in Sport, 2025)
The purpose of this study was to assess the reliability of a series of lateral hops for both performance and lower extremity kinematics. Between-session reliability study. University Laboratory. 20 subjects (11 male, 9 females) 25.14 ± 2.77 years, 72.97 ± 9.73 kg, and 169.44 ± 7.23 cm. Participants completed four lateral hops, altering their takeoff and landing legs. We quantified hop distance and 2-dimensional frontal and sagittal plane kinematics at peak knee flexion. Testing was performed on two occasions, with a mean difference of 7 days apart. Interclass correlation coefficients and paired t-tests were performed to compare reliability and differences in outcome measures across the two sessions, p <.05. All four lateral hops had good to excellent reliability (ICC 0.84–0.91), with no statistical difference in hop distance between days, p >.05. Sagittal plane kinematics had good to excellent reliability (ICC 0.86–0.95) however frontal plane kinematics showed moderated to good reliability (ICC 0.54–0.90). A battery of lateral hopping tasks has moderate to excellent reliability for both performance and kinematics, suggesting their use by clinicians and in clinical practice. • Forward hopping is a common method to quantify lower extremity function. • Lateral hopping distance demonstrates good to excellent reliability. • Sagittal kinematics were more reliable than frontal kinematics during lateral hops.